Exploring Customer Readiness Level and Preferences for Private Electric Passenger Cars in Kerala - Praveen P.M (International Journal of Social Sciences, Language and Linguistics, 2025)
Decisions related to vehicle purchase are influenced by various factors including purchase price, total cost of ownership, fuel efficiency, maintenance cost, and resale value. In India, the dominance of fossil fuel-powered vehicles has led to several environmental and economic challenges. Increasing fuel prices not only strain individual budgets but also contribute to inflation, impacting the national economy. Consequently, renewable, reusable, and sustainable alternatives have become imperative. Electric vehicles (EVs), widely adopted in many foreign countries, offer a promising solution. This study focuses on understanding the customer perspective on the adoption of electric passenger cars in Kerala, aiming to uncover awareness levels, preferences, and barriers to adoption.